Education for sustainable development – planning the direction of education in the field of information technologies - Sokołowski, Adam (Edukacja dla zrównoważonego rozwoju. Planowanie kierunku kształcenia w obszarze technologii informacyjnych, 2021)
The paper was mainly intended to establish whether parents of children aged between 7 and 14 are interested in teaching them modern information technologies, and to develop an adequate methodology for evaluating the children’s aptitude in the process of teaching these issues. The survey questionnaire was addressed to 1,116 parents of children aged between 7 and 14. As suggested by the research, there is a considerable interest in the process of children’s education and development of their digital competence regarding the following IT spheres: computer graphics, programming, and animation. The paper also presents the concept of a diagnostic platform, which will contribute to the adequate profiling of the didactic material in terms of the students’ predispositions through an interactive mode of observations. The presented concept can also bear an auxiliary function when potentially determining the further developmental path of the child.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 3 (61), s. 32-45
Keywords: education for sustainable development; aptitude assessment; eye-tracking; edukacja dla zrównoważonego rozwoju; ocena predyspozycji; eye tracking